Who Was Naamah?: Insights from Robert Crumb's The Book of Genesis Illustrated - Friedmann, Jonathan L. (Journal of religion and popular culture, 2019)
Robert Crumb's The Book of Genesis Illustrated (2009) attempts a verse-by-verse rendering of all fifty chapters of the Book of Genesis. This includes meticulous illustrations of genealogical lists and "throw-away" characters. Crumb breathes life into the passing names, giving them personalities and placing them in life situations. This article examines the single-panel portrait of Naamah (Genesis 4:22), the sister of primordial founders of human civilization. Although she is merely a name in the biblical text, Crumb makes her a proud and captivating songstress in the mould of Miriam, sister of Moses. The drawing epitomizes the role of the illustrator as an interpreter, blending elements of rabbinic exegesis with Crumb's own interests in folk music, powerful women, and the "dimly remembered matriarchy" of biblical times.